EFFECT OF PATIENT-CENTERED CARE ON SERVICE QUALITY AND SATISFACTION LEVEL OF BPJS INPATIENTS IN BAPTIST HOSPITAL BATU - Pradani, Estri Aditya; Rohman, Fatchur; Siswanto, Siswanto (Jurnal Aplikasi Manajemen, 2018)
This study aims to determine the effect of PCC implementation and its relation to patient satisfaction, either directly or indirectly, with the quality of service as mediating factor. This research is an explanatory research with cross-sectional approach. This study aims to determine the effect of (1) PCC implementation, (2) technical service quality, (3) functional service quality, and (4) patient satisfaction level. The study was conducted during March-April 2017 in inpatient unit of Baptism Batu Hospital, with the sample of 100 people. Data were collected using questionnaires measuring the perception of patients using a 5-point Likert scale. Data were analyzed using SMART-Partial Least Square. PCC has a direct effect on service quality, but it was not significant. PCC had an indirect effect on patient satisfaction, especially through functional service quality. Overall, functional service qualitydirectly affected patient satisfaction with the greatest total effect. PCC should be implemented with respect to service quality to create patient satisfaction.